2007
DOI: 10.1152/ajpgi.00287.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inducible cAMP early repressor suppresses gastrin-mediated activation of cyclin D1 and c-fosgene expression

Abstract: Steigedal TS, Bruland T, Misund K, Thommesen L, Laegreid A. Inducible cAMP early repressor suppresses gastrin-mediated activation of cyclin D1 and c-fos gene expression. Am J Physiol Gastrointest Liver Physiol 292: G1062-G1069, 2007. First published December 21, 2006; doi:10.1152/ajpgi.00287.2006.-The gastric hormone gastrin and its precursors promote proliferation in several gastrointestinal cell types. Here we show that gastrin induces transcription of cell cycle gene cyclin D1 and protooncogene c-fos in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…The evidence that ICER acts as a tumor suppressor gene in leukemia cell line HL60, as reported previously for other solid tumors, [28][29][30] first comes from the decreased clonogenicity ability of HL60 þ ICER cells in vitro. We used immunodeficent mice to confirm these data and reveal that HL60 þ ICER-injected mice have a mild leukemia phenotype for the reduced dissemination of tumor in extramedullary sites.…”
Section: Discussionsupporting
confidence: 65%
“…The evidence that ICER acts as a tumor suppressor gene in leukemia cell line HL60, as reported previously for other solid tumors, [28][29][30] first comes from the decreased clonogenicity ability of HL60 þ ICER cells in vitro. We used immunodeficent mice to confirm these data and reveal that HL60 þ ICER-injected mice have a mild leukemia phenotype for the reduced dissemination of tumor in extramedullary sites.…”
Section: Discussionsupporting
confidence: 65%
“…We and others have previously shown that c-fos is activated by gastrin [23], [31], [32], and we thus wanted to explore a possible role of SIK1 in gastrin-induced c-fos activation. AGS-G R cells with ectopically expressed SIK1 showed a two-fold increase in gastrin-induced c- fos- luc transcription compared to control cells (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Cells (5.0×10 5 /well) in six-well plates were harvested in 0.5 ml SDS-sample buffer and subjected to western blot analysis as described previously [23]. Binding of secondary antibodies was visualized by the Super Signal West Femto Maximum Sensitivity Substrate (Pierce, Rockford, IL) and Kodak Image Station 2000R (Kodak, Pittsburgh, PA).…”
Section: Methodsmentioning
confidence: 99%
“…We (Ref. 53 and unpublished data), as well as others (55), have shown that gastrin induces expression of genes encoding members of the AP-1 complex, like c-fos and junB. To investigate AP-1 as a possible mediator of gastrin-induced expression of clusterin, AR42J cells were transfected with reporter plasmids containing the luciferase gene driven by the rat clusterin promoter with or without the AP-1 site.…”
Section: Gastrin Increases Expression Of Clusterin In Adenocarcinoma mentioning
confidence: 99%